The Influence of Milling on the Structural and Morphological Properties of Waste-Based Active Carbon from Rubber Seeds Using High Energy Milling (HEM) Method - Arsyad, Fitri Suryani; Aprilianda; Aulia; Akmal Johan; Ihsan Alfikro; Amiruddin Supu; Ahmad, Nur; Andrivo Rusydi (Science and Technology Indonesia, 2026)
The high-energy milling (HEM) synthesis method has produced activated carbon powder from rubber ore shell waste. The activated carbon was prepared using a chemical method with activation temperatures varying between 400, 500, and 600°C. Temperature optimization resulted in activated carbon with a maximum carbon content at 600°C. The activated carbon was then milled for various times: 0, 30, 60, and 90 minutes. The crystallinity and surface morphology of the samples were then confirmed using an X-ray diffractometer (XRD) and scanning electron microscope (SEM) characterization. Based on the XRD graph, the percentage of structural regularity, or degree of crystallinity, of the activated carbon tended to decrease from 18.17% without milling treatment to 17.52% at 30 minutes of milling, 17.45% at 60 minutes of milling, and 17.35% at 90 minutes of milling. SEM images also show a decrease in the average pore diameter from approximately 0.45 µm to 0.20 µm with a more homogeneous intraparticle morphology structure when the milling time is increased from 30 minutes to 90 minutes. This study demonstrates the potential of rubber seed shell waste for processing into activated carbon. The HEM method can significantly reduce the grain size of activated carbon and increase its surface area and reactivity, making it more effective in applications as an adsorbent and filter.